Effect of Supplementary Video Information on Patient Anxiety Before Urodynamic Testing: A Randomized Controlled Study - Mehmet Şahin; Murat Gürbüz; Metin Savun; Yiğit Can Filtekin; Osman Can; Halil Lutfi Canat (International Neurourology Journal)
Purpose Urodynamic testing, a minimally invasive procedure commonly performed in urology, often induces preprocedure anxiety due to its invasive nature and insufficient preparatory information. This study investigated whether supplementing traditional verbal and written explanations with video‐animated information could help reduce anxiety in patients undergoing urodynamic testing. Methods In this randomized, controlled, prospective study, patients were divided into 2 groups: a nonvideo group (n=100), which received only verbal and written explanations, and a video group (n=100), which additionally viewed an animated informational video. Anxiety was assessed using the State-Trait Anxiety Inventory: the trait version (STAI-T) for general anxiety and the state version (STAI-S), administered both before and after information delivery, for situational anxiety. Results Median STAI-T scores did not differ significantly between groups (P=0.067). While preinformation STAI-S scores were comparable (P=0.702), postinformation STAI-S scores were significantly higher in the nonvideo group (group 2) compared to the video group (P<0.001). In the video group (group 1), the median STAI-S score decreased from 34 (range, 20–62) preinformation to 26 (range, 20–39) postinformation (P<0.001). In group 2, the median STAI-S score decreased from 35 (range, 20–63) to 28 (range, 22–48) (P<0.001). Patients who received video-animated information exhibited a significantly larger reduction in STAI-S score (median change, 6.5 vs. 5.0; P=0.034), suggesting greater anxiety relief with video supplementation. Conclusions Adding video‐animated information to conventional verbal and written explanations significantly increases anxiety reduction before urodynamic testing, potentially improving patient comfort and understanding of the procedure.